A catered st. patrick's day ebook - Crawford, Isis (A Mystery with Recipes, 2012)
"Cozy fans will appreciate the zany characters, witty dialogue and puzzling plot."— Publishers Weekly To most of the people of Longely, New York, St. Paddy's Day means good food, great music, and plenty of Guinness. But when the lifeless body of Mike Sweeney floats to the top of a vat of green beer, it looks like the luck o' the Irish has just run out. Unfortunately for the Simmons sisters, Bernie and Libby, the number one suspect is related to one of their very best catering customers, the pampered and powerful Bree Nottingham. When Bree visits A Little Taste of Heaven to beseech them to clear her nephew's name, they just can't say no. But the more information Bernie and Libby stir up, the more Duncan Nottingham looks like a killer. For Bernie and Libby, the situation is in danger of boiling over. And they can't count on good old Saint Pat to drive out the snake in their midst...they'll have to do it themselves. "Fans of culinary cozies by Joanne Fluke and Diane Mott Davidson will enjoy discovering Crawford."— Library Journal Includes original recipes for you to try!